THE PROBLEM OF FORMING MANAGEMENT COMPETENCE OF FUTURE SPECIALISTS IN INSTITUTIONS OF HIGHER EDUCATION - Кайкова, М.; Троян, Н. (Modern engineering and innovative technologies, 2024)
The article presents the formation of managerial competence among future specialists in the conditions of a higher school. Competence is understood as an integral property of individuality. Features of managerial competence of future specialists in modern